PELATIHAN PEMBUATAN JAMU JAHE WANGI DARI TOGA SEBAGAI IMMUN BOOSTER PADA KELOMPOK IBU-IBU PKK DI DESA SURAT KECAMATAN MOJO - Munifatul Lailiyah (Jurnal Bakti untuk Negeri, 2022)
Medicinal plants can be used as raw materials for herbal medicine. Medicinal plants can grow freely anywhere. One of the villages that has extensive agricultural land and a lot of agricultural products, including abundant local plants, is Surat Village, Mojo District. Surat Village is one of the villages located in Mojo District, Kediri Regency, most of the people in Surat Village have knowledge about the potential of local plants in this village. The purpose of this socialization is to educate villagers about the potential of local plants to be developed into herbal medicineThe implementation of this socialization activity consists of three methods such as; observation, socialization, and demonstration of how to make herbal medicine, the herbal medicine made is ''jamu ginger fragrant'' based on the socialization activity, many villagers enthusiastically participated in the activity, there were some people who were interested in using local plants to make herbal medicine, and all the spectators can understand how to make healthy drinks or ginger-based herbs The final result of this socialization, it can be concluded that the socialization of how to make fragrant ginger herbs from local plants in Surat Village was a success, the villagers were very enthusiastic, and the audience knew how to make fragrant ginger herbs. This socialization is expected to increase the community's ability to understand how herbal medicine is produced from medicinal plants in Surat village.